Modelling and Analysis of Thermoelectric and Oscillating Water System as Low Carbon Emission Renewable Energy Resources in Indonesia - Samuel Tanuwijaya (Jurnal Syntax Admiration, 2024)
Energy, as an inexhaustible phenomenon, undergoes transformations through various forms to meet human needs. Some forms of energy are challenging to harness for reuse, necessitating a combination of energy generators to enhance electricity production from renewable sources such as heat and water. The utilization of Ocean Wave Energy Converter (OWC) emerges as one solution, harnessing the phenomena of waves and air pressure to drive generators. The generated electrical output does not have to be large, as long as it can produce heat through coils. This heat is then used to warm thermoelectric materials, generating electricity that can be stored in the Powerhouse Storage. A holistic approach is employed to harness renewable energy efficiently and sustainably to meet electrical needs.